L‐carnitine supplementation vs cycle ergometer exercise for physical activity and muscle status in hemodialysis patients: A randomized clinical trial. Issue 3 (3rd September 2020) - Yano, Junko; Kaida, Yusuke; Maeda, Takashi; Hashida, Ryuki; Tonan, Tatsuyuki; Nagata, Shuji; Hazama, Takuma; Nakayama, Yosuke; Ito, Sakuya; Kurokawa, Yuka; Otome, Takaomi; Shibata, Ryo; et al.
Abstract: Serum carnitine is decreased in hemodialysis patients, which induces muscle atrophy. Thus, we examined the different effects of l ‐carnitine and exercise on exercise activity and muscle status in hemodialysis patients. Twenty patients were divided into l ‐carnitine and cycle ergometer groups and were followed for 3 months. Muscle and fat mass, physical activities, and muscle status were evaluated by an impedance, physical function test, and magnetic resonance imaging, respectively. The l ‐carnitine significantly increased muscle mass ( P = .023) and thigh circumference ( P = .027), decreased fat mass ( P = .007), and shortened chair stand‐up time ( P = .002) and 10‐m walk test ( P = .037). The fat fraction was improved by the l ‐carnitine ( P = .047). Compared with the exercise group, l ‐carnitine improved the changes in 10‐m walk test ( P = .026), chair stand‐up time ( P = .014), and thigh circumference ( P = .022). Baseline fibroblast growth factor‐21 and myostatin levels predicted the l ‐carnitine‐associated changes in exercise activities. l ‐carnitine, rather than exercise, improved physical activity and muscle status in hemodialysis patients.